EFECTO DE ABONOS ORGÁNICOS EN EL RENDIMIENTO DEL CULTIVO DE FREJOL NEGRO (Phaseolus vulgaris) VARIEDAD BRUNCA EN EL SECTOR PORTAL DEL LAGO, PARROQUIA CHIGÜILPE, CANTÓN SANTO DOMINGO, PROVINCIA SANTO DOMINGO DE LOS TSÁCHILAS - Paredes Vargas, Edwin Guillermo (2015)
This research was carried out on the farm of Mr. Edwin Paredes located at Km 3.5 via Santo Domingo -. Aloag in the Portal area of the lake belongs to the canton Santo Domingo, Santo Domingo Province of Tsáchilas. The research was aimed at assessing "ORGANIC FERTILIZER EFFECT ON THE PERFORMANCE OF BLACK bean crop (Phaseolus vulgaris) BRUNCA VARIETY IN THE SECTOR PORTAL DEL LAGO, Chiguilpe PARISH, CANTON SANTO DOMINGO, and PROVINCE SANTO DOMINGO. Using three types of organic fertilizers with similar doses. The objective of this paper is to analyze the effect of organic fertilizers, calculating the return on cultivating black bean (Phaseolus vulgaris), to know the farmers in the area this experience and multiply in culture. The methodology applied in this study randomized block design with their respective comparisons in each of the variables studied. Settling four treatments with four replicates for a total of sixteen experimental units (plots) where manure produced as were applied: (Bocashi of pig droppings), (Bocashi chicken manure) and (Bocashi Bovine) using a single dose treatment each subscription. The variables were evaluated in each treatment, days to flowering, plant height, plant height, pods per plant, grains per pod, production per hectare, rentabilidad.Se fertilizer made an application located at the base of the hole at planting at the base of the plant preventing comes into contact with the root. The results were; Flowering days the witness had the highest number of days (33.0); The highest point of the plant reached T3 (46 cm); the largest number of pods per plant 9.8 to T3; Number of grains per pod T1 and T3 6.9 Increased production and eventually T3 with 2672.5 kg / ha. It is concluded that in this trial, it is necessary to implement and promote the use of organic fertilizers to reward farmers' productivity Portal Lake sector. We recommend applying solid organic fertilizers because they provide nutrients, also favor the improvement of structure and soil structure, they are very economical, increase production significantly and are safe for human consumption.